Familial clustering of unexplained heart failure - A Danish nationwide cohort study. (19th May 2022) - Glinge, C; Rossetti, S; Bruun Oestergaard, L; Stampe, NK; Ravn Jacobsen, M; Koeber, L; Engstroem, T; Torp-Pedersen, C; Gislason, G; Jabbari, R; Tfelt-Hansen, J
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): This project has received funding from the European Union's Horizon 2020 research and innovation programme under acronym ESCAPE-NET, registered under grant agreement No 733381, and the European Union's COST programme under acronym PARQ, registered under grant agreement No CA19137. Background: Although family history of heart failure (HF) is associated with increased risk of HF, the extent to which a family history contributes to the risk of HF needs further investigation. Purpose: To determine whether a family history of unexplained HF in first-degree relatives (children or sibling) increases the rate of unexplained HF. Methods: Using Danish nationwide registry data (1978-2017), we identified patients (probands) diagnosed with first unexplained HF (HF without any known comorbidities) in Denmark, and their first-degree relatives. All first-degree relatives were followed from the HF date of the proband and until an event of unexplained HF, exclusion diagnosis, death, emigration, or study end, whichever occurred first. Using the general population as a reference, we calculated adjusted standardized incidence ratios (SIR) of unexplained HF in the three groups of relatives using Poisson regression models. Results: We identified 57, 845 first-degree relatives to individuals previously diagnosed with unexplained HF. Having a family history was associated with a significantly increased unexplained HF rate of 2.08 (95% CI 1.82-2.38) (Figure 1 ). The estimate was higher among siblings (SIR 4.82 [95% CI 3.17-7.32]). Noteworthy, the rate of HF increased for all first-degree relatives when the proband was diagnosed with HF in a young age (≤50 years, SIR of 3.60 [95% CI 2.37-5.47]) and having >1 proband (SIR of 2.73 [95% CI 1.14-6.56]). The highest estimate of HF was observed if the proband was ≤40 years at diagnosis (6.12 [95% CI 3.39-11.05]) (Figure 2 ). Conclusion: A family history of unexplained HF was associated with a two-fold increased rate of unexplained HF among first-degree relatives. If the proband age was ≤40 years, the risk was six-folded. These findings suggest that screening families of unexplained HF with onset below 50 years is indicated.